Ontological absence and speculative presence in Palestinian Science Fiction. - Mattar, Netty (2021)
Economic and technological globalization has created concerns that affect all of humanity. Transformations of space and time, the media’s hyperrealization of reality, and hypermodern capitalism, for example, are experienced by societies across the world. Speculative fiction (sf) is a genre that adequately expresses this new reality. While sf has often been regarded as the preserve of the west, it is increasingly regarded as a global phenomenon. As more diverse cultures embrace sf, more hybrid forms of the genre have emerged involving dissonant ontologies. I am interested in how these competing ontologies come together in Palestinian sf. Palestinian sf writers employ sf conventions that recast the ethos of modernity rooted in Western Enlightenment. These signifiers and referents, therefore, turn towards the West—elsewhere. However, the signified—who the works address—is the Palestinian people, who have been largely disregarded by the West and excluded from its discourse. The Palestinians have an ambiguous ontology, their identities, their past, and their ongoing struggles for self-determination silenced. Palestinian sf therefore is something of a contradiction: sf has become a way for Palestinian writers to bring what has been silenced and erased into present consciousness, but through a language that already turns away from them. Reading a selection of Palestinian sf short stories from the collection Palestine +100, I ask what the relationship between absence and presence is in Palestinian sf. I ask how the aesthetics of absence functions in Palestinian sf to evoke that which has been silenced in Palestinian history. In doing so, I examine how Palestinian sf challenges traditional oppositions between east and west, absence and presence, and replaces them by more nuanced and mixed concepts. I show how Palestinian sf thereby gestures towards shared histories and topologies of pain that lie outside of normative (Western) experience.